Interactions with family members in students’ dreams - Nöltner, Sandra; Schredl, Michael (Dreaming, 2023)
The present study examined the frequency of core family members (mother, father, brother, and sister) in dreams and their interactions with the dreamer. The dreams were collected via dream diaries. Dream content was analyzed using the Hall and Van de Castle rating system. Overall, 28.9% of the 1,612 dreams reported by 425 participants (361 females and 64 males) included at least one member of the core family. The mother as a single figure appeared most often (13.4%). The father and “parents” as a unit occurred the second most (7.6%), followed by sister (7.6%), and the brother occurred the rarest (5.1%). Comparing the dream interactions with the parents, the dreamers were more aggressive against their mothers and received more friendliness from their fathers. Interactions with brothers and sisters were similar, except that more frequent indirect interactions happened with brothers. There was more verbal interaction and more aggression between dream self and his or her parents compared with siblings. Overall, there was no sexual interaction and almost no physical aggression with family members. As our findings are in line with the literature about family interactions in waking life, they support the continuity hypothesis of dreaming. (PsycInfo Database Record (c) 2023 APA, all rights reserved)
Gesehen am 15.07.2024